2020
DOI: 10.3390/jmse8100733
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative IMTA System: Polychaetes, Sponges and Macroalgae Co-Cultured in a Southern Italian In-Shore Mariculture Plant (Ionian Sea)

Abstract: In this paper, we report data from the first year of rearing of a set of filter feeder bioremediator organisms: macrobenthic invertebrates (sabellid polychaetes and sponges), coupled with macroalgae, realized in a mariculture fish farm. This innovative integrated multi-trophic aquaculture (IMTA) system was realized at a preindustrial level in the Gulf of Taranto (southern Italy, northern Ionian Sea), within the framework of the EU Remedia Life project. Long lines containing different collector typologies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 94 publications
(131 reference statements)
0
55
0
Order By: Relevance
“…In conclusion, we provided evidence that S. spinosulus is able to remove the inoculated V. parahaemolythicus from seawater in test tanks at different concentrations, showing better performance at the higher concentration, with a contribution to the nutrient load. The promising survival and growth performance already obtained by this species in a Mediterranean IMTA system [49] highlights the ability of this sponge species to withstand the environmental conditions of an aquaculture facility. In addition, the biomass obtained [49] appears to be sufficient to implement the rearing system over time, thus avoid-ing ethical problems due to the depletion of wild stocks.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In conclusion, we provided evidence that S. spinosulus is able to remove the inoculated V. parahaemolythicus from seawater in test tanks at different concentrations, showing better performance at the higher concentration, with a contribution to the nutrient load. The promising survival and growth performance already obtained by this species in a Mediterranean IMTA system [49] highlights the ability of this sponge species to withstand the environmental conditions of an aquaculture facility. In addition, the biomass obtained [49] appears to be sufficient to implement the rearing system over time, thus avoid-ing ethical problems due to the depletion of wild stocks.…”
Section: Discussionmentioning
confidence: 80%
“…The promising survival and growth performance already obtained by this species in a Mediterranean IMTA system [49] highlights the ability of this sponge species to withstand the environmental conditions of an aquaculture facility. In addition, the biomass obtained [49] appears to be sufficient to implement the rearing system over time, thus avoid-ing ethical problems due to the depletion of wild stocks. S. spinosulus represents an effective mediator and bioremediator in integrated multitrophic aquaculture systems.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There has been a renewed interest in farming of sponges in situ due to the outstanding filtering abilities of sponges and to replenish natural populations of bath sponge stocks . The ecosystem services provided by sponges in diverse marine habitats, together with their ability to contain and accumulate biomaterials have raised interest in the inclusion of these animals in integrated multitrophic aquaculture (IMTA) applications and in use of treatment of waste water streams (Cebrian et al 2003;Page et al 2005Longo et al 2016;Gokalp et al 2019Gokalp et al , 2020aGiangrande et al 2020). In this integrated farming approach, sponges consume dissolved and particulate nutrients available in the water column without the need for additional feeding providing a triplet benefit: 1) enhanced production of sponge biomass, 2) prevention of overexploitation from natural stocks and 3) purified water, whether the organic particle load is from suspended fish farm activities or urban runoff .…”
Section: Introductionmentioning
confidence: 99%
“…A series of long-lasting culture trials revealed several factors that determine the prosperity and sustainability of the culture. These include biotic factors such as predation by marine organisms, diseases and fouling, species-related factors such as broodstock selection and repeated cloning, as well as abiotic factors including water temperature, seasonality/time of seeding and external factors such as storms, wave action, marine traffic and vandalism (Barthel and Theede 1986;Duckworth and Battershill 2003;Page et al 2005Giangrande et al 2020).…”
Section: Introductionmentioning
confidence: 99%